Impact of off-pump coronary artery bypass grafting on survival: current best available evidence - Chivasso, Pierpaolo; Guida, Gustavo A.; Fudulu, Daniel; Bruno, Vito D.; Marsico, Roberto; Sedmakov, Hristo; Zakkar, Mustafa; Rapetto, Filippo; Bryan, Alan J.; Angelini, Gianni D. (Journal of Thoracic Disease, 2016)
The superiority of either off-pump (OPCAB) or on-pump (ONCAB) coronary artery bypass grafting (CABG) remains unclear despite a large body of literature evidence comparing the two approaches. The potential advantages of avoiding cardiopulmonary bypass (CPB), minimizing aortic manipulation and maintaining pulsatile flow may be associated with reduced inflammatory responses and embolic events. Numerous studies compared OPCAB with ONCAB and the cumulative data have been presented in meta-analyses of both randomized and observational studies. Although there is an abundance of data with respect to the operative morbidity and mortality and the short-term outcomes associated with these two strategies, not much is known about how they impact long-term survival and recurrence of myocardial ischaemic events. Recent studies and meta-analyses have focused on long-term survival and major secondary outcomes in OPCAB vs. ONCAB within the general population. Significant limitations in methodology, however, have raised concerns about the strength of several randomized trials with restrictive inclusion criteria that reduced the populations to those at low risk only, thus creating result bias. Here, we present a review of the best available evidence with a focus on long-term outcomes.